EFFECTIVENESS OF THE @APVI.OFFICIAL INSTAGRAM ACCOUNT IN ACCORDANCE TO FULFILL FOLLOWERS' INFORMATION NEEDS - Arrafi, Muhamad Iman; Farid; Sari, Wulan Purnama; Jonathan, Maureen (ASPIKOM Jabodetabek Region, 2022)
Instagram @apvi.official is a social media account for spreading content that focuses on information about vape. Informative content uploaded to the Instagram account @apvi.official in the form of photos and videos about the world of vape. The goal to be achieved in this research is to find out how effective it is in fulfilling information needs on the Instagram @apvi.official page. Descriptive qualitative is the method chosen in this writing with Instagram followers @apvi.official as the population in the study with 100 respondents taken as a sample based on the results of the slovin formula. The analysis technique used is descriptive analysis, continuum line, simple linear regression, t test and coefficient of determination. The total percentage results are 83.5%, the percentage points are between 68% and 84% which means high. So, it was concluded that the t test results obtained a p-value of 0.001, in other words the result is less than 0.005, which means the effectiveness of Instagram @apvi.official activities is active in fulfilling the information needed by its followers.